Perancangan E-Commerce Penjualan Brankas Berbasis Website (Studi Kasus: CV. BINTANG UTAMA) - Hario Febrian Pratama; Irawan, Bambang; Hario, Hario Febrian Pratama Subekti (Research and Community Service UNIVERSITAS KALBIS, 2025)
Bintang Utama is a company specializing in safes, striving to enhance services and quality through a customer-oriented business strategy. Currently, product marketing is limited to social media platforms like a company website and whatsApp, necessitating the development of a new marketing medium: e-commerce. This research aims to design a web-based e-commerce platform for selling safes to expand marketing reach. Data was collected through observation, interviews, and literature studies, with development utilizing the RAD (Rapid Application Development) method, UML, PHP, and MySQL. The results show that the e-commerce platform was successfully developed, with all features functioning optimally based on black box testing. The website has been implemented and is accessible to both existing customers and new users interested in purchasing safes from CV. Bintang Utama.